(untitled) (Journal of the Bangladesh Agricultural University, 2016)
The study was conducted to assess the impact of conservation agriculture practice on crop profitability in Bangladesh and to identify the determinants of adopting such practice. A total of 300 farmers (50 focal, 100 proximal and 150 control) from five districts (Mymensingh, Bogra, Tangail, Sherpur and Jamalpur) were selected. Focal farmers were selected purposively; and proximal and control farmers were selected randomly. Descriptive statistics like sum, averages, percentages and ratios were calculated to evaluate the socioeconomic data. Profitability of crop production was measured in terms of gross return, gross margin, net return and benefit cost ratio (BCR). Crop productivity was measured using the Enyedis crop productivity index. The BCR of focal, proximal and control farmers were 2.58, 2.24 and 2.18, respectively. The crop productivity of focal, proximal and control farmers were increased by 0.5, 1.1 and 1.4 percent, respectively with respect to the entire region. Educational level of household head, farm size, farm income, extension contact and farming experience were found as significant factors through logit model that affect the adoption of this practice by the farmers. Input support, motivation, training programmes and extension services by different government and non-government organizations should be properly organized and implemented to raise the consciousness and enhance the knowledge of the farmers on conservation agriculture practice. J. Bangladesh Agril. Univ. 14(1): 101-112, June 2016